Effect of letrozole 2.5 mg or 5.0 mg for ovulation induction in intrauterine insemination in case of unexplained infertility: a randomized controlled trial - Goel, Neha; Verma, Ashok; Bansal, Shubham; Kumari, Manjeet; Drishti; Deeksha (International Journal of Research in Medical Sciences, 2023)
Background: Aim was to compare effects of letrozole 2.5 mg or 5.0 mg for ovulation induction in patients with unexplained Infertility. Methods: A randomized controlled trial. 60 patients attending infertility clinic were randomly allocated into two groups-Group A received letrozole 2.5 mg and Group B received letrozole 5 mg orally for 5 days from 3rd day of cycle. The patients also received inj FSH 75 IU i/m on day 7 and 9 of the cycle and underwent follicular study on day 11, 13, 15. When the dominant follicle size reached 18 mm ovulation triggered with Inj hCG 5000 IU IM and Intrauterine insemination was done 24-36 hours later. Pregnancy rates were calculated. Results were analysed by statistical software. Results: Better ovulation rates were seen in patients receiving 5 mg letrozole. No difference in the pregnancy rates was found between the two groups. No multiple pregnancies and ovarian hyperstimulation seen. Conclusions: It appears that 5 mg daily for 5 days is a preferable letrozole dose for superovulation.